Evolving Paradigms in Research and Care in Ovarian Cancers. Issue 4 (October 2016) - Karlan, Beth Y.; Alvarez, Ronald D.; Strauss, Jerome F.
Abstract : The National Academies of Sciences, Engineering, and Medicine convened an expert committee to examine and summarize the state of the science in ovarian cancer research. An Executive Summary of the recently released report describing the key findings and specific recommendations to reduce the incidence of and morbidity and mortality from ovarian cancers is presented. Highlights include the recognition that ovarian cancer is not just one disease, but rather a constellation of distinct cancer types, some of which originate outside of the ovary. Furthermore, it was noted that our incomplete understanding of the basic biology of each subtype of ovarian cancer is an impediment to advances in prevention, screening, early detection, diagnosis, treatment, and supportive care. Abstract : Key findings and recommendations from the National Academies of Sciences, Engineering, and Medicine's recent report on the state of the state of the science of ovarian cancer research are presented.